Psychological factors influencing laypersons’ acceptance of climate engineering, climate change mitigation and business as usual scenarios - Klaus, Geraldine; Ernst, Andreas; Oswald, Lisa (Technology in society, 2020)
In the past two decades, research on so-called climate engineering approaches has increased. These technologies are considered to be potential substitutes for mitigation strategies in combating climate change. The ongoing process of layperson acceptance and resultant opinion formation can be expected to play a crucial role in future public debate about field experiments or the actual deployment of climate engineering. In July 2017, we assessed public reactions from the German population in a representative online survey. Participants were given a brief text informing them about climate change and one of four different scenarios in a between-subject design (N = 678). Two of the scenarios described the use of climate engineering technologies - stratospheric aerosol injection (SAI) and bio-energy with carbon capture and storage (BECCS) - one of them covered conventional mitigation strategies and the fourth group was given an outline of the business-as-usual (BAU) approach. The mitigation scenario (willingness for individual behaviour changes) showed the highest acceptance rate (M = 74.23), which was significantly higher than acceptance of the other scenarios (p < .001). Acceptance of BECCS (M = 53.15) was higher than acceptance of SAI (M = 46.25, p = .043) and BAU (M = 42.94; p = .006). We undertook a relative-importance analysis to investigate the influence of multiple predictor variables on acceptance formation for each scenario; the variance thus explained ranged from 80.3% to 86.8%. The results point up the influence of perceived risks, subjective norms and affective responses on the acceptance of climate engineering technologies. By contrast, person-specific and relatively stable variables, such as environmental attitudes and wishful thinking, are particularly relevant in the evaluation of the mitigation scenario. •Mitigation scenarios are more accepted than business as usual or climate engineering scenarios to combat climate change.•Concerning climate engineering, bio-energy with carbon capture and storage is preferred over stratospheric aerosol injection.•Technology acceptance is driven by situational judgements like affective responses, perceived fairness or trust.•Mitigation acceptance depends more on problem perception, eco-friendly attitudes and relativization of climate change threats.•Subjective norms are highly relevant for the acceptance of all scenarios.